(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Literary and numismatic data show that the Carthaginian army organization could have been based on the klerouchia Ptolemaic institution during their conquest and administration of Iberia. Possibly the Barca family settled active mercenaries with ownership and use of lands on two precise strategical areas, the Beturia Túrdula and the hinterland of Gades, the two areas where the coinage that we have called “libiofenician” by its epigraphical and linguistic anomalies is minted. Probably the bronze of Lascuta, a Libiophoenician city, testify this process.